«Zemlja neznaema» i iranskij substrat «Slova o polku Igoreve» The Unknown Land and the Iranian Substratum in the Tale of Igor’s Campaign - Rakhno, Kostyantyn (Studia mythologica Slavica, 2014)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This article deals with the semantics of the image of the Unknown Land in the Tale of Igor’s Campaign. It is proposed to examine it in the light of the warriors’ classification of lands peculiar to the Ossetians and reflected in the Ossetian Nart sagas. The ancestors of the modern Ossetians, the Alans, were the closest neighbours and allies of the Slavic population of the Kievan Rus. Therefore many folklore motifs and religious conceptions of the Iranian peoples are present in the above-mentioned epic poem, including the direct parallels with the Nart epos. Some characters of the poem, for example, the bard Boyan, who turns into a weasel, a wolf or an eagle and is apostrophized as Veles’s grandson, could not be explained correctly without bringing the Ossetian epic and mythology into the picture.